Cooling and Refrigeration Solar Systems - Ali Ahmeed Ali Alrabee (Surman Journal of Science and Technology, 2023)
Photovoltaic (PV) Energy Systems and Thermal Energy Systems have been used for decades for the purposes of generating electricity and thermally needed processes. These systems are expanding more and more every year alongside the emerging new researches results aiming at the development of the different systems to provide the needs of cooling and refrigeration fields in general. This report will present the different available methods, materials and system's design of the cooling and refrigeration. Although in practice solar cooling and refrigeration are nearly the same process, but usually either the material, the methods or temperature ranges are different.